The Influence of Promotion via Social Media Instagram and Facebook on Purchase Interest among Generation Y at the FP Bali Hotel, Kuta - Yudhawijaya, Made; Pitanatri, Putu Diah Sastri; Adyatma, Prastha (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the impact of promotions through Instagram and Facebook on the purchase intention of generation Y at the FP Bali Hotel, Kuta. The quantitative method was used by distributing questionnaires to 100 Instagram and Facebook followers of the hotel who are generation Y. The data analysis process used multiple linear regression procedures on SPSS version 27.0. The findings show that the purchase intention of generation Y is significantly and positively influenced by product promotions on Instagram and Facebook, both individually and simultaneously. The management of FP Bali Hotel is expected to be able to utilize these findings as input to increase purchase intention through the implementation of appropriate promotion strategies.